Використання архівних ресурсів у суспільстві: інформаційно-аналітичне дослідження - Вовк, Наталія; Демків, Христина; Даниляк, Ольга (Видавництво Львівської політехніки, 2016)
This article discusses the description of archival institutions and archival sources using modern society. Prompting the survey that was conducted in order to obtain results relating to archives and archive a whole. There are possible ways of presentation of archival institutions, so as to encourage people to visit the archives and to treat them the opportunity to familiarize themselves with various document resources.
Keywords: archive; archival institution; archival documents; visiting archives; the quality of the archives right